MO296MEAN PLATELET VOLUME IN FAMILIAL MEDITERRANEAN FEVER RELATED AMYLOIDOSIS AND COMPARISON WITH COMMON PRIMARY GLOMERULAR DISEASES. (29th May 2021) - Yildirim, Tolga; Kutahya, Berranur; Is, Fatma; Erdevir, Mehmet; Uzerk Kibar, Muge; Koc, Neriman Sila; Saglam, Arzu; Yilmaz, Seref Rahmi; Erdem, Yunus
Abstract: Background and Aims: Compared to healthy controls, mean platelet volume (MPV) is frequently higher in patients with Familial Mediterranean fever (FMF) but lower in amyloidosis patients. The cause of differing MPV levels in FMF patients with and without amyloidosis is not clear. We hypothesized that severe proteinuria and renal dysfunction in amyloidosis could be responsible from low MPV in contrast to FMF patients without amyloidosis. We aimed to compare MPV levels of FMF patients with amyloidosis and MPV values of patients with different glomerular diseases to understand if low MPV is unique to amyloidosis or MPV is similar in all glomerular diseases indicating that it is a consequence of proteinuria and/or renal dysfunction. Method: We compared pre-biopsy MPV levels of patients with amyloidosis secondary to FMF, to MPV levels of patients with membranous glomerulonephritis, focal segmental glomerulosclerosis (FSGS) and IgA nephropathy that all present with proteinuria and renal dysfunction. Factors affecting MPV were also determined. Results: 703 patients (411 male, 292 female) were included in the study. Mean age was 42.6±14.3 years. There were 124 patients with amyloidosis, 224 patients with IgA nephropathy, 188 patients with membranous glomerulonephritis and 167 patients with FSGS. Patients with amyloidosis had lower MPV compared to patients without amyloidosis (7.9±1.2 fL vs. 8.2±0.9 fL respectively, p=0.008). Patients with amyloidosis had also significantly lower MPV compared to patients with each of the other diagnoses. MPV was negatively correlated with platelet count (r = - 0.351, p <0.001). There was no significant correlation of MPV with serum creatinine and proteinuria. Conclusion: This study is the largest study of MPV in patients with biopsy proven amyloidosis and confirms previous studies reporting low MPV in amyloidosis. This study indicates that low MPV in amyloidosis cannot be explained with severe proteinuria and renal dysfunction.